Supplementing the lack of ubuntu? The ministry of Zimbabwe"s Mashoko Christian Hospital to people living with HIV and AIDS in challenging their stigmatisation in the church - Banda, Collium (HTS teologiese studies, 2019)
This article uses the African communal concept of ubuntu to reflect on the ministry of Mashoko Christian Hospital (MCH), Zimbabwe, to people living with the human immunodeficiency virus (HIV) and AIDS (PLWHA) during the early days since the discovery of the disease. The main question this article seeks to answer is: from a perspective of the African philosophy of ubuntu, how did the ministry of MCH to PLWHA challenge the fear and judgemental attitudes towards the disease within the Churches of Christ in Zimbabwe? This leads to another question: what should the churches learn from MCH’s response to HIV and AIDS? This article only focusses on trends in conduct and not on a detailed history of engaging HIV and AIDS. The significance of this article is to demonstrate the important role played by faith-based organisations (FBOs) in complementing the compassion and care often lacking in the official churches’ response to HIV and AIDS.